THE EFFECTIVENESS OF LEVOFLOXACIN 0.5% WITH POVIDONE IODINE 2.5% IN REDUCING CONJUNCTIVA BACTERIAL FLORA IN PRE INTRA OCULAR OPERATIVE: Oral Presentation - Experimental Study - Ophthalmologist - OKTA KURNIAWAN SAPUTRA (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : This study aims to compare the effectiveness of Levofloxacin ED 0.5% with Povidone iodine 2.5% in reducing normal bacterial flora of the conjunctiva in preoperative procedures. Methods : Clinical trials will be conducted in the inpatient ward on patients who will undergo intravitreal surgery at Mohammad Hoesin Hospital Palembang from May 2022-July 2022. Subjects were divided into two groups, which is Levofloxacin ED 0.5% and Povidone iodine 2.5% group. Before and after the fornices preparation, the number of bacterial colonies that grow will be counted and evaluated using bivariate analysis. Results : There were 32 samples that fulfilled the inclusion criteria. A significant decrease of conjunctival flora was observed in both groups (p value = 0.000). Comparison of the two groups’ decrease in conjunctival flora was not significant. There was a reduction of up to 100% in 11 samples (68.75%) of both intervention groups. Conclusion : The use of Levofloxacin 0.5% and Povidone iodine 2.5% was equally good in reducing the number of bacterial colonies in the conjunctiva.